Cumulative Impact of HIV and Multiple Concurrent Human Papillomavirus Infections on the Risk of Cervical Dysplasia. (22nd February 2016) - Adler, David H.; Wallace, Melissa; Bennie, Thola; Abar, Beau; Meiring, Tracy L.; Williamson, Anna-Lise; Bekker, Linda-Gail
Abstract : Infection with HIV is known to increase the risk of cervical cancer. In addition, evidence suggests that concurrent infection with multiple human papillomavirus (HPV) genotypes increases the risk of cervical dysplasia more than infection with a single HPV genotype. However, the impact of the combination of HIV coinfection and presence of multiple concurrent HPV infections on the risk of cervical dysplasia is uncertain. We compared the results of HPV testing and Pap smears between HIV-infected and HIV-uninfected young women to assess the cumulative impact of these two conditions. We found that both HIV and the presence of multiple concurrent HPV infections are associated with increased risk of associated Pap smear abnormality and that the impact of these two risk factors may be additive.